Rebuilding livelihoods after dam-induced relocation in Koga, Blue Nile basin, Ethiopia - Irit Eguavoen; Weyni Tesfai (University of Bonn, Center for Development Research (ZEF), 2011)
For the past years, Ethiopia has been moving toward making better use of the waters from the Blue Nile. The Koga project is the first new large]scale irrigation scheme in the river basin since the 1970s. The article analyzes the social]economic outcome of development]induced relocation of 500 relocated households, in particular the sub]set which moved to the nearby town. The delay in land re]allocation had left households without livelihood base for much longer than expected and compensation payments were not sufficient to bridge the critical period. Households tended to maintain their social network and memberships in supportive rural associations after relocation but poverty acted as constraint in some cases, especially when households did not find other income generating activities. Housing in town was made difficult due to the need to legalize land exchange arrangements. And it required a common interest (security) to initiate social relations between town dwellers and newcomers. – – Seit einigen Jahren ist Äthiopien bestrebt, seine Wasserressourcen des Blauen Nils besser nutzbar zu machen. Das Koga Bewässerungsprojekt ist das erste neue Großdammprojekt im Flussbecken seit den 1970er Jahren. Der Artikel analysiert die sozialen und ökonomischen Folgen für die 500 Haushalte, die wegen des Entwicklungsprojektes umsiedeln mussten, inbesondere der Gruppe, die in die nahe Stadt gezogen ist. Verzögerungen in der Landumverteilung entzog den Bauern für eine längere Periode als erwartet die Lebensgrundlage, was nicht ausreichend durch Kompensationszahlungen aufgefangen werden konnte. Die Haushalte tendierten dazu, ihre sozialen Netzwerke und Mitgliedschaften in ländlichen Unterstützungsvereinen nach der Umsiedlung beizubehalten. Allerdings war Armut ein Hindernis für einige Haushalte, die keine neuen Einkommensquellen erschlossen hatten. Die Wohnsituation in der Stadt wurde durch die vorgeschriebene Legalisierung von Landtauscharrangements erschwert. Und es brauchte ein gemeinsames Interesse (Sicherheit), um soziale Beziehungen zwischen Stadtbewohnern und Neuankömmlingen zu initiieren.
Keywords: 330; Nile; irrigation; development-induced displacement; livelihood